2014
DOI: 10.1080/02640414.2014.981849
|View full text |Cite
|
Sign up to set email alerts
|

The ingestion of a caffeinated energy drink improves jump performance and activity patterns in elite badminton players

Abstract: The aim of this study was to investigate the effectiveness of a caffeine-containing energy drink to enhance physical and match performance in elite badminton players. Sixteen male and elite badminton players (25.4 ± 7.3 year; 71.8 ± 7.9 kg) participated in a double-blind, placebo-controlled and randomised experiment. On two different sessions, badminton players ingested 3 mg of caffeine per kg of body mass in the form of an energy drink or the same drink without caffeine (placebo). After 60 min, participants p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
62
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 26 publications
8
62
0
3
Order By: Relevance
“…Regarding the impact of supplementation on cycling performance, the present study concluded that energy drinks' consumption was associated with better performance in both endurance (p = 0.001) and speed races (p = 0.001), a finding which comes in agreement with other studies in cyclists showing that performance was improved with energy drinks comparing to placebo [1,24,37]. We should bare in mind that energy drinks should be consumed in rational proportions as to act in favor of exercise, otherwise they may become dangerous, causing hypertension, cardiac dysrhythmias, tachycardia or heart failure [17,24,71].…”
Section: Discussionsupporting
confidence: 91%
“…Regarding the impact of supplementation on cycling performance, the present study concluded that energy drinks' consumption was associated with better performance in both endurance (p = 0.001) and speed races (p = 0.001), a finding which comes in agreement with other studies in cyclists showing that performance was improved with energy drinks comparing to placebo [1,24,37]. We should bare in mind that energy drinks should be consumed in rational proportions as to act in favor of exercise, otherwise they may become dangerous, causing hypertension, cardiac dysrhythmias, tachycardia or heart failure [17,24,71].…”
Section: Discussionsupporting
confidence: 91%
“…The duration and degree of the standardization protocols differed among studies. The duration whereby participants had to abstain from all dietary sources of alcohol, caffeine and other stimulants ranged from the day itself [36,40] to 24 hours [35][36][37][41][42][43][44][45], 48 hours [34,38,39,[46][47][48][49][50] and the entire study duration (2 sessions separated by 1 week) [51]. Participants were also asked to adopt a similar diet and fluid intake level the day before each experimental trial.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of activity levels, participants were advised to avoid all strenuous exercise the day before each trial to minimize any muscle soreness and fatigue. Only in studies were participants involved in a light and standardized training session the day before each trial [44,49,50]. No information on pre-trial standardization and procedures was reported in 3 studies [34,37,45].…”
Section: Resultsmentioning
confidence: 99%
“…performing a squat jump). Previous studies (Abian et al., 2015; Bloms, Fitzgerald, Short, & Whitehead, 2016; Del Coso et al., 2014; Pérez‐López et al., 2015) have shown an increased squat jump height after caffeine ingestion. However, these studies did not include a pre‐capsule measurement and, therefore, these data should be interpreted with caution, because day‐to‐day variability was not controlled (for example, in our study squat jump height had a day‐to‐day coefficient of variation of 5.2%).…”
Section: Discussionmentioning
confidence: 92%